SALES GROWTH MEMODERASI PENGARUH TRANSFER PRICING, THIN CAPITALIZATION DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Joy Imanuela Soukotta (2023)
The purpose of this study was to determined and analyze sales growth in moderating the effect of transfer pricing, thin capitalization and capital intensity on tax avoidance. This study uses a sample of manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in the2018-2020 period. The sampling technique used in this study is purposive sampling with a sample acquisition of 60 companies. This study uses a quantitative method using panel data. The data analysis technique in this study used classical assumption test, model selection test, multiple linear regression, and hypothesis testing. The result of this study indicate that transfer pricing and thin capitalization are not have a significant effect on tax avoidance, capital intensity have a significant effect on tax avoidance, then sales growth are able to moderate the relationship between capital intensity to tax avoidance, and sales growth are not able to moderate the relationship between transfer pricing and thin capitalization to tax avoidance.